2022
DOI: 10.4103/jos.jos_141_21
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of Icon resin infiltration and Clinpro XT varnish on remineralization of white spot lesions

Abstract: OBJECTIVE: To compare the efficacy of Icon resin infiltration and Clinpro XT varnish on remineralization of white spot lesions using a polarized light microscope (PLM). MATERIALS & METHODS: Artificial white spot lesions were created on a sample of 40 extracted human premolar teeth by immersing in a demineralizing solution. All samples were randomly allocated to two groups of 20 each; Group A: Icon resin infiltration and Group B: Clinpro XT varnish. Teeth were sectioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The focal point of these ionic exchanges is based on the epitaxial deposition of calcium and phosphate ions on existing apatite crystallites. Many materials, including fluoride varnishes such as Duraphat, glass ionomer-based materials, Regenerate, infiltrating resins and MI paste promote enamel remineralization 16 , 17 , 18 , 19 , 20 . These materials release calcium and fluoride ions that promote the obliteration of pores 16 and regularization of the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…The focal point of these ionic exchanges is based on the epitaxial deposition of calcium and phosphate ions on existing apatite crystallites. Many materials, including fluoride varnishes such as Duraphat, glass ionomer-based materials, Regenerate, infiltrating resins and MI paste promote enamel remineralization 16 , 17 , 18 , 19 , 20 . These materials release calcium and fluoride ions that promote the obliteration of pores 16 and regularization of the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…No systematic review or meta-analysis of this subject area was found. All included articles were conducted in Egypt,[ 17 18 19 ] Korea,[ 20 ] USA,[ 18 21 ] Saudi Arabia,[ 22 ] India,[ 23 24 25 26 ] Germany,[ 8 21 , 27 28 29 ] Chile,[ 30 ] Brazil,[ 10 11 , 31 32 ] Romania,[ 33 ] and Switzerland. [ 26 ]…”
Section: R Esultsmentioning
confidence: 99%
“…All the reviewed articles were in vitro , describing a total of 1836 teeth. In 23 studies, 8 studies used natural enamel lesions,[ 8 20 , 21 27 28 29 , 33 34 ] 15 studies created artificial WSLs,[ 10 17 18 19 , 22 23 24 25 26 30 31 32 , 35 36 37 ] and 3 studies used bovine enamel. [ 10 32 , 35 ] To measure the penetration depth, most of the articles used confocal laser scanning microscopies (CLSM) (18 studies),[ 8 10 , 17 18 , 20 21 22 25 , 27 28 29 31 32 33 34 35 36 37 ] followed by polarized light microscopy (one study),[ 23 ] scanning electron microscopy (SEM) (one study),[ 30 ] stereomicroscope (two studies)[ 19 26 ] and optical profilometer (one study).…”
Section: R Esultsmentioning
confidence: 99%
See 2 more Smart Citations